Three novel patients with epileptic encephalopathy due to biallelic mutations in the PLCB1 gene. Issue 3 (15th January 2020) - Desprairies, Camille; Valence, Stéphanie; Maurey, Hélène; Helal, Suzette I.; Weckhuysen, Sarah; Soliman, Hala; Mefford, Heather C.; Spentchian, Myrtille; Héron, Delphine; Leguern, Eric; Nava, Caroline; Bouilleret, Viviane; et al.
Abstract: Biallelic mutations in the PLCB1 gene, encoding for a phospholipase C beta isoform strongly expressed in the brain, have been reported to cause infantile epileptic encephalopathy in only four children to date. We report here three additional patients to delineate the phenotypic and genotypic characteristics of the disease. Our three patients were one sporadic case with an intragenic homozygous deletion and two cousins with the homozygous p.(Arg222*) nonsense variant in PLCB1 . These patients had severe to profound intellectual disability, epileptic spasms at age 3‐5 months concomitant with developmental arrest or regression, other seizure types and drug‐resistant epilepsy. With this report, we expand the clinical, radiologic and electroencephalographic knowledge about the extremely rare PLCB1 ‐related encephalopathy. Since the first report in 2010, the overall number of reported patients with our additional patients is currently limited to seven. All seven patients had epileptic encephalopathy, mainly infantile spasms and 6/7 had profound intellectual disability, with one only being able to walk. Truncal hypotonia was the most frequent neurological sign, sometimes associated with pyramidal and/or extrapyramidal hypertonia of limbs. Microcephaly was inconstant. In conclusion, the phenotypical spectrum of PLCB1 ‐related encephalopathy is relatively narrow, comprises infantile spasms and severe to profound intellectual disability, and does not seem to define a recognizable clinical entity. Abstract :